2016
DOI: 10.1007/s00401-016-1647-9
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic proteins complexin-I and complexin-II differentially influence cognitive function in early and late stages of Alzheimer’s disease

Abstract: Progressive accumulation of Alzheimer's disease-related pathology is associated with cognitive dysfunction. Differences in cognitive reserve may contribute to individual differences in cognitive function in the presence of comparable neuropathology. The protective effects of cognitive reserve could contribute differentially in early versus late stages of the disease. We investigated presynaptic proteins as measures of brain reserve (a subset of total cognitive reserve), and used Braak staging to estimate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 57 publications
(107 reference statements)
3
34
3
Order By: Relevance
“…However, one can be more or less resilient relative to the average person and therefor have a slower or faster rate of residual cognitive decline. We found several genomic and neurobiologic indices of resilience were associated with a slower rate of decline including presynaptic proteins, neuron density, and BDNF expression [122, 132137]. We are also finding genes associated with a faster rate of cognitive decline [138].…”
Section: Resultsmentioning
confidence: 99%
“…However, one can be more or less resilient relative to the average person and therefor have a slower or faster rate of residual cognitive decline. We found several genomic and neurobiologic indices of resilience were associated with a slower rate of decline including presynaptic proteins, neuron density, and BDNF expression [122, 132137]. We are also finding genes associated with a faster rate of cognitive decline [138].…”
Section: Resultsmentioning
confidence: 99%
“…1). Ramos-Miguel et al have also detected higher levels of CPLX1 in the OML than in the IML [37]. Albeit both IML and OML contains mainly excitatory inputs to GC, the afferent input is, to a large extent distinct and arises from mossy cells of the CA4 (called associational/commissural projections) and EC layer II, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…CPLX1 is a presynaptic protein known as SNARE complex‐binding protein which plays an important role in vesicle release promoting synchronization of Ca 2+ triggered vesicle fusion and inhibiting spontaneous vesicles release (Lai et al, ). Downregulation of CPLX1 is associated with impaired basal synaptic strength and short‐term plasticity (Chang et al, ), and more recently decreased CPLX1 levels have been suggested as a significant risk factor associated with AD and Parkinson's disease (Lahut et al, ; Ramos‐Miguel et al, ). Our results further support the importance of CPLX1 for the maintenance of basal synaptic activity and short‐term plasticity and provide new evidence on the involvement of this protein in neurodegenerative disorders associated with tau pathology.…”
Section: Discussionmentioning
confidence: 99%